MARKETING OPPORTUNITIES IN SUPPLY CHAIN DEVELOPMENT IN SMALL BUSINESSES - Abduvaxobov Boburmirzo Botirovich PhD student at Samarkand Institute of Economics; Service (SCIENCE AND INNOVATION IDEAS IN MODERN EDUCATION, 2024)
This article examines the role and importance of marketing strategies in the process of developing a supply chain in small businesses. The role of marketing activities in improving the efficiency of the supply chain, meeting customer needs, and ensuring competitiveness is analyzed. It also highlights the development opportunities of small businesses through market analysis, effective communication with customers, and the use of innovative marketing methods.